a,x² + 4x + 4 = 7 + 9y²
x² + 4x - 3 = 9y²
x² + 4x - 3 = 0(1)
9y² = x² + 4x - 3(2)
Giai pt 1 :
a = 1, b = 4, và c = -3. Thay vào công thức: x = (-(4) ± √((4)² - 4(1)(-3))) / (2(1)) x = (-4 ± √(16 + 12)) / 2 x = (-4 ± √28) / 2 x = (-4 ± 2√7) / 2 x = -2 ± √7
Giai pt 2
9y² = (-2 + √7)² + 4(-2 + √7) - 3 9y² = 4 - 4√7 + 7 + (-8 + 4√7) - 3 9y² = 0
Vậy, phương trình x² + 4x+ 4 - 9y² = 7 có hai nghiệm là x = -2 + √7 hoặc -2 - √7 và y = 0.
b,
(x² + 4x + 4 - 9y²) + (x² + 2x - y² + 6y) = 7 + 9 2x² + 6x - 10y² + 6y + 4 = 16
x² + 4x + 4 - 9y² = 7 x² + 4x - 9y² - 3 = 0
x = (-4 ± √(4² - 4(1)(-9y² - 3))) / (2(1)) x = (-4 ± √(16 + 36y² + 12)) / 2 x = (-4 ± √(36y² + 28)) / 2 x = (-4 ± 2√(9y² + 7)) / 2 x = -2 ± √(9y² + 7)
(x² + 2x - y² + 6y) = 9 (-2 ± √(9y² + 7))² + 2(-2 ± √(9y² + 7)) - y² + 6y = 9 (4 ± 4√(9y² + 7) + 9y² + 14 - y² + 6y) = 9 8√(9y² + 7) + 8y² + 20y + 18 = 9 8√(9y² + 7) + 8y² + 20y + 9 = 0